Technology and Learner Autonomy: An Argument in Favor of the Nexus of Formal and Informal Language Learning. (March 2019) - Lai, Chun
Abstract: This article discusses some of the current research on technology in relation to learner autonomy, outlining major findings on the relationship between technology and learner autonomy in formal and informal learning contexts. Extant literature has discussed both teacher-initiated technology-enhanced formal learning environments and learner-constructed self-directed learning experience in informal learning contexts. Although valuable in the insights it provides into how technology aids learner autonomy, the two bodies of literature have largely been independent from each other, which may constrain our understanding.